Variation in the Stabilimenta of Cyclosa fililineata Hingston, 1932, and Cyclosa morretes Levi, 1999 (Araneae: Araneidae), in Southeastern Brazil - Marcelo O. Gonzaga; João Vasconcellos-Neto (Psyche: A Journal of Entomology)
We investigated the characteristics of the stabilimenta constructed by two species of Cyclosa, describing the variations within and among five populations. Both species constructed stabilimenta composed entirely of silk (linear and spiral types) or of silk and debris (linear, detritus clusters and complex types). The vertical linear detritus type was the most frequent structure for adult females of both species, whereas stabilimenta consisting of detritus clusters were more frequent for juveniles of C. morretes. The latter structures appeared to be an intermediate state towards the linear continuous type usually found in adults. The other types were rarely found, and silk stabilimenta were to be constructed only when detritus was not available. The substitution of silk by detritus indicated that both materials function as camouflage in C. morretes and C. fililineata webs. The positions occupied by the spiders within the detritus column (and in some cases the orientation of the stabilimenta) varied markedly within populations, and the unpredictability of their location could be important in reducing the risks of predation. The hypothesis that stabilimenta constitute defensive devices was indirectly corroborated by the observation that spider’s body width and length were, respectively, strongly correlated with the width and length of the stabilimenta.